Alternative finance in the international business context: a review and future research - Allen, Franklin; Qian, Meijun (Journal of International Business Studies, 2025)
Abstract Firms increasingly rely on alternative finance (AF) in addition to banks and equity markets, and its usage across countries differs significantly. We conceptualize AF as financing that operates within social, business, and virtual networks that generate informational, collateral, and incentive advantages compared to finance relying on traditional financial intermediaries. Examples of AF include family loans, microfinance, trade credit, community credit cooperatives, person-to-person (P2P), and crowdfunding. While AF is not a new phenomenon, technological development continues to facilitate its increasing prominence. We review the evolution of AF theories, summarize key empirical findings, and describe how AF intersects with international business (IB) research. Specifically, we review how AF feeds into the analysis of comparative financial systems, financial development, comparative corporate governance, and national culture. We conclude that AF has shaped comparative research in IB in important ways, but cross-border research in IB has hardly considered the role of AF. Globalization and technological development and adoption in the financial industry generate rich fields where AF and IB intersect; these have yet to be understood. We describe how IB research, specifically addressing the cross-border dimension, could benefit from integrating insights from AF research, and propose approaches to integrate theories on AF, IB, and internationalization.